Quantitative analysis of cryptic splicing associated with TDP-43 depletion - Jack Humphrey; Warren Emmett; Pietro Fratta; Adrian M. Isaacs; Vincent Plagnol (BMC, 2017)
Abstract Background Reliable exon recognition is key to the splicing of pre-mRNAs into mature mRNAs. TDP-43 is an RNA-binding protein whose nuclear loss and cytoplasmic aggregation are a hallmark pathology in amyotrophic lateral sclerosis and frontotemporal dementia (ALS/FTD). TDP-43 depletion causes the aberrant inclusion of cryptic exons into a range of transcripts, but their extent, relevance to disease pathogenesis and whether they are caused by other RNA-binding proteins implicated in ALS/FTD are unknown. Methods We developed an analysis pipeline to discover and quantify cryptic exon inclusion and applied it to publicly available human and murine RNA-sequencing data. Results We detected widespread cryptic splicing in TDP-43 depletion datasets but almost none in another ALS/FTD-linked protein FUS. Sequence motif and iCLIP analysis of cryptic exons demonstrated that they are bound by TDP-43. Unlike the cryptic exons seen in hnRNP C depletion, those repressed by TDP-43 cannot be linked to transposable elements. Cryptic exons are poorly conserved and inclusion overwhelmingly leads to nonsense-mediated decay of the host transcript, with reduced transcript levels observed in differential expression analysis. RNA-protein interaction data on 73 different RNA-binding proteins showed that, in addition to TDP-43, 7 specifically bind TDP-43 linked cryptic exons. This suggests that TDP-43 competes with other splicing factors for binding to cryptic exons and can repress cryptic exon inclusion. Conclusions Our quantitative analysis pipeline confirms the presence of cryptic exons during the depletion of TDP-43 but not FUS providing new insight into to RNA-processing dysfunction as a cause or consequence in ALS/FTD.